2014
DOI: 10.1186/s40490-014-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of adjuvants to improve uptake of phosphorous acid applied to Pinus radiata needles for control of foliar Phytophthora diseases

Abstract: Background: Phosphorous acid is being investigated as a fungicide for the management of a needle disease caused by Phytophthora pluvialis in Pinus radiata in New Zealand. However, little is known about the penetration characteristics of this fungicide into Pinus radiata foliage. This study was undertaken to determine: i) the penetration characteristics of a commercial phosphorous acid formulation, applied at 3 kg ha -1 and 12 kg ha -1 in 100 L water, into Pinus radiata foliage and, ii) the effect of four comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…ha −1 were diluted with deionized water from a commercial formulation of Agrifos ® 600 (Key Industries Ltd., Auckland, New Zealand; 600 g l −1 H 2 (PO 3 H) l −1 present as potassium phosphite, adjusted to pH 5.7–6.0). Each phosphite concentration was mixed with a 0.2% organosilicone‐blend containing siloxane polyalkyleneoxide copolymers (Du‐Wett ® , Etec Crop Solutions Ltd, Auckland, New Zealand) in accordance with manufacturer recommended concentrations, as per Rolando et al () and applied within 20 min after mixing. Phosphite was applied using a calibrated, moving head track‐sprayer operated at 401 kPa at an average boom speed of 3.0 m s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ha −1 were diluted with deionized water from a commercial formulation of Agrifos ® 600 (Key Industries Ltd., Auckland, New Zealand; 600 g l −1 H 2 (PO 3 H) l −1 present as potassium phosphite, adjusted to pH 5.7–6.0). Each phosphite concentration was mixed with a 0.2% organosilicone‐blend containing siloxane polyalkyleneoxide copolymers (Du‐Wett ® , Etec Crop Solutions Ltd, Auckland, New Zealand) in accordance with manufacturer recommended concentrations, as per Rolando et al () and applied within 20 min after mixing. Phosphite was applied using a calibrated, moving head track‐sprayer operated at 401 kPa at an average boom speed of 3.0 m s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Phosphite does not kill or eradicate Phytophthora species but suppresses the pathogen's activity while simultaneously boosting the plant's natural defense responses, at concentrations in planta that only partially inhibit pathogen growth in vitro (Smille et al , Hardy et al , Wilkinson et al ). Phosphite has had successful use in the management of Phytophthora diseases in agriculture, forestry and natural ecosystems, in Europe (Fernandez‐Escobar et al ), United States (Garbelotto et al ), Australia (Ali et al , Barrett et al , Shearer et al , ) and New Zealand (Reglinski et al , Horner and Hough , Rolando et al ). In field applications, foliar phosphite treatment has also been shown to directly reduce the rate of spread of Phytophthora pathogens within naturally infested, florally diverse ecosystems (Shearer et al ), and is a valuable tool in the containment and quarantine response to new Phytophthora incursions (Hardy et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Screening is underway to identify resistance within current radiata pine breeding lines in use in New Zealand . Phosphoric acid (phosphite) and copper have both shown promise for the control of P. pluvialis within plantation systems, but are yet to be applied operationally within New Zealand forest systems (Ganley et al, 2014;Rolando et al, 2014).…”
Section: Forest and Wildland Hosts And Symptomsmentioning
confidence: 99%
“…wileyonlinelibrary.com/journal/efp and preventative properties. Rolando, Gaskin, Horgan, Williams, and Bader (2014) demonstrated that phosphite (also referred to as phosphonate) can be effective in limiting infection of P. radiata by P. pluvialis and P. kernoviae. However, it is not known whether formulations containing systemic fungicides, such as phosphite or metalaxyl-M, will be more or less effective than protectants such as the copper-based fungicides in controlling Phytophthora disease in P. radiata plantations.…”
Section: Introductionmentioning
confidence: 99%